Structural characterization of framework–gas interactions in the metal–organic framework Co2(dobdc) by in situ single-crystal X-ray diffraction. Issue 6 (27th April 2017) - Gonzalez, Miguel I.; Mason, Jarad A.; Bloch, Eric D.; Teat, Simon J.; Gagnon, Kevin J.; Morrison, Gregory Y.; Queen, Wendy L.; Long, Jeffrey R.
Abstract : In situ single-crystal X-ray diffraction experiments enable the direct observation of weak metal–gas interactions in a metal–organic framework. Abstract : The crystallographic characterization of framework–guest interactions in metal–organic frameworks allows the location of guest binding sites and provides meaningful information on the nature of these interactions, enabling the correlation of structure with adsorption behavior. Here, techniques developed for in situ single-crystal X-ray diffraction experiments on porous crystals have enabled the direct observation of CO, CH4, N2, O2, Ar, and P4 adsorption in Co2 (dobdc) (dobdc 4− = 2, 5-dioxido-1, 4-benzenedicarboxylate), a metal–organic framework bearing coordinatively unsaturated cobalt(ii ) sites. All these molecules exhibit such weak interactions with the high-spin cobalt(ii ) sites in the framework that no analogous molecular structures exist, demonstrating the utility of metal–organic frameworks as crystalline matrices for the isolation and structural determination of unstable species. Notably, the Co–CH4 and Co–Ar interactions observed in Co2 (dobdc) represent, to the best of our knowledge, the first single-crystal structure determination of a metal–CH4 interaction and the first crystallographically characterized metal–Ar interaction. Analysis of low-pressure gas adsorption isotherms confirms that these gases exhibit mainly physisorptive interactions with the cobalt(ii ) sites in Co2 (dobdc), with differential enthalpies of adsorption as weak as −17(1) kJ mol −1 (for Ar). Moreover, the structures of Co2 (dobdc)·3.8N2, Co2 (dobdc)·5.9O2, and Co2 (dobdc)·2.0Ar reveal the location of secondary (N2, O2, and Ar) and tertiary (O2 ) binding sites in Co2 (dobdc), while high-pressure CO2, CO, CH4, N2, and Ar adsorption isotherms show that these binding sites become more relevant at elevated pressures.